Acute (R,S)-Ketamine Administration Induces Sex-Specific Behavioral Effects in Adolescent but Not Aged Mice - Mastrodonato, Alessia; Pavlova, Ina; Kee, Noelle; McGowan, Josephine C.; Mann, J. John; Denny, Christine A. (Frontiers in Neuroscience, 2022)
(R,S)-ketamine is an N-methyl-D-aspartate (NMDA) receptor antagonist that was originally developed as an anesthetic. Most recently, (R,S)-ketamine has been used as a rapid-acting antidepressant, and we have reported that (R,S)-ketamine can also be a prophylactic against stress in adult mice. However, most pre-clinical studies have been performed in adult mice. It is still unknown how an acute (R,S)-ketamine injection influences behavior across the lifespan (e.g., to adolescent or aged populations). Here, we administered saline or (R,S)-ketamine at varying doses to adolescent (5-week-old) and aged (24-month-old) 129S6/SvEv mice of both sexes. One hour later, behavioral despair, avoidance, locomotion, perseverative behavior, or contextual fear discrimination (CFD) was assessed. A separate cohort of mice was sacrificed 1 hour following saline or (R,S)-ketamine administration. Brains were processed to quantify the marker of inflammation Cyclooxygenase 2 (Cox-2) expression to determine whether the acute effects of (R,S)-ketamine were partially mediated by changes in brain inflammation. Our findings show that (R,S)-ketamine reduced behavioral despair and perseverative behavior in adolescent female, but not male, mice and facilitated CFD in both sexes at specific doses. (R,S)-ketamine reduced Cox-2 expression specifically in ventral CA3 (vCA3) of male mice. Notably, (R,S)-ketamine was not effective in aged mice. These results underscore the need for sex- and age-specific approaches to test (R,S)-ketamine efficacy across the lifespan.